NUTRITIONAL STATUS OF CHRONIC KIDNEY FAILURE PATIENTS HAVING CYCLE HEMODIALYSIS AT DUC GIANG GENERAL HOSPITAL (Vietnam Journal of Community Medicine, 2024)
Objectives: To describe the nutritional status of patients with chronic renal failure undergoingdialysis at Duc Giang General Hospital in 2022-2023.Methods: The cross-sectional study was conducted on 174 patients with chronic renal failure patientsundergoing dialysis at Duc Giang General Hospital from August 2022 to February 2023.Results: The nutritional status according to the weight loss index accounted for nearly 6%, of which5.2% was moderate weight loss, while 0.6% was severe weight loss. Nutritional status according toBMI was 63.8% with normal BMI, BMI
Keywords: Nutritional status, chronic kidney failure patients having cycle hemodialysis, Duc Giang General Hospital.